T cell interactions with microglia in immune-inflammatory processes of ischemic stroke - Yuxiao Zheng; Zilin Ren; Ying Liu; Juntang Yan; Congai Chen; Yanhui He; Yuyu Shi; Fafeng Cheng; Qingguo Wang; Changxiang Li; Xueqian Wang (2024)
The primary mechanism of secondary injury after cerebral ischemia may be the brain inflammation that emerges after an ischemic stroke, which promotes neuronal death and inhibits nerve tissue regeneration. As the first immune cells to be activated after an ischemic stroke, microglia play an important immunomodulatory role in the progression of the condition. After an ischemic stroke, peripheral blood immune cells (mainly T cells) are recruited to the central nervous system by chemokines secreted by immune cells in the brain, where they interact with central nervous system cells (mainly microglia) to trigger a secondary neuroimmune response. This review summarizes the interactions between T cells and microglia in the immune-inflammatory processes of ischemic stroke. We found that, during ischemic stroke, T cells and microglia demonstrate a more pronounced synergistic effect. Th1, Th17, and M1 microglia can co-secrete pro-inflammatory factors, such as interferon-γ, tumor necrosis factor-α, and interleukin-1β, to promote neuroinflammation and exacerbate brain injury. Th2, Treg, and M2 microglia jointly secrete anti-inflammatory factors, such as interleukin-4, interleukin-10, and transforming growth factor-β, to inhibit the progression of neuroinflammation, as well as growth factors such as brain-derived neurotrophic factor to promote nerve regeneration and repair brain injury. Immune interactions between microglia and T cells influence the direction of the subsequent neuroinflammation, which in turn determines the prognosis of ischemic stroke patients. Clinical trials have been conducted on the ways to modulate the interactions between T cells and microglia toward anti-inflammatory communication using the immunosuppressant fingolimod or overdosing with Treg cells to promote neural tissue repair and reduce the damage caused by ischemic stroke. However, such studies have been relatively infrequent, and clinical experience is still insufficient. In summary, in ischemic stroke, T cell subsets and activated microglia act synergistically to regulate inflammatory progression, mainly by secreting inflammatory factors. In the future, a key research direction for ischemic stroke treatment could be rooted in the enhancement of anti-inflammatory factor secretion by promoting the generation of Th2 and Treg cells, along with the activation of M2-type microglia. These approaches may alleviate neuroinflammation and facilitate the repair of neural tissues.